2004
DOI: 10.1007/s00134-004-2511-2
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral vs. enteral nutrition in the critically ill patient: a meta-analysis of trials using the intention to treat principle

Abstract: Intention to treat trials demonstrated reduced mortality associated with parenteral nutrition use. A priori subgroup analysis attributed this reduction to trials comparing parenteral to delayed enteral nutrition. Despite an association with increased infectious complications, a grade B+ evidence-based recommendation (level II trials, no heterogeneity) can be generated for parenteral nutrition use in patients in whom enteral nutrition cannot be initiated within 24 h of ICU admission or injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
204
5
19

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(231 citation statements)
references
References 64 publications
3
204
5
19
Order By: Relevance
“…Specifically, we observed neither the trend towards decreased mortality nor the increase in infectious complications previously reported for patients fed via the parenteral route. [2][3][4] It is possible that the lack of an infectious burden from feeding via the parenteral route is because of improvements in central venous catheter management (CALORIES data indicate a low incidence of catheter-related and bloodstream infections); 60 delivery and composition of feed; and avoidance of overfeeding and hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, we observed neither the trend towards decreased mortality nor the increase in infectious complications previously reported for patients fed via the parenteral route. [2][3][4] It is possible that the lack of an infectious burden from feeding via the parenteral route is because of improvements in central venous catheter management (CALORIES data indicate a low incidence of catheter-related and bloodstream infections); 60 delivery and composition of feed; and avoidance of overfeeding and hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Meta-analyses of the trials comparing nutritional support via the enteral and parenteral route in critically ill patients have been published, but interpretation of their results is complicated by small sample size, poor methodological quality, select groups of critically ill patients studied, lack of standardised definitions for outcome measures and interventions combining more than one element of nutritional support, for example timing and route.…”
Section: Background and Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…However, the ENT started later may have deleterious results 8 . In a meta-analysis 12 , Simpson and Doig (2005) demonstrated that the survival of critically ill patients (including trauma victims) was higher in patients undergoing early PNT versus late ENT (OR 0.29, 95% CI 0.12-0.70).…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%